Kompetensi Aparatur Desa, Moralitas, Sistem Pengendalian Internal, dan Pencegahan Fraud Pengelolaan Dana Desa - Rakanti, Ni Putu Tarisa Putri; Ratnadi, Ni Made Dwi (Jurnal Akuntansi Bisnis, 2024)
This research examines the effect of the competence of village apparatus, morality and internal control system on fraud prevention of village fund management. This research was conducted in 58 villages in Tabanan Regency, Bali. Each village was selected by three people namely village head, village secretary and treasurer from a total sample of 174 respondents. The results of this analysis show that the competence of village apparatus, morality, and internal control system have a positive effect on fraud prevention in village fund management. The practical implications obtained from the results of this study are to provide information that can prevent fraud in the management of village funds, namely, the competence of village officials related to their knowledge, skills, and behaviors. Morality by increasing self-control to act in ethical matters such as not using power for personal gain, fear of sanctions and considering the principles of public welfare. Adequate internal control system by improving the control environment, risk assessment, information and communication as well as internal control monitoring.